Perencanaan Reklamasi Pada Lahan Bekas Penambangan Timah di PT Berkat Berjaya Sejahtera, Kabupaten Bangka - Ramadhan, Setiawan; Irvani, Irvani; Andini, Delita Ega (Universitas Negeri Gorontalo, 2023)
One of the companies engaged in tin mining is PT Berkat Berjaya Sejahtera with reclamation planning from 2013 to 2022 with a planned land area of 10 Ha. However, the available area exceeds the planned area of 11.08 Ha. Based on these problems, the purpose of this research is to plan reclamation techniques and reclamation cost plans so that reclamation activities can run effectively and efficiently. The method used in this research is quantitative method. The data taken are soil pH and water pH data, topographic data (x, y, z coordinates). Data processing is carried out using a drone tool which is processed using surpac, minescape and surfer software. Based on the results of the research that has been carried out, it can be concluded that the reclamation technique plan is carried out by land stewardship by closing the void starting from elevation 2 to elevation 11 masl and leveling the land area to be reclaimed. The type of plant used in reclamation is oil palm the costs required for this reclamation are divided into 2, namely, Direct Costs and Indirect Costs. Direct costs required amount to Rp 1,326,572,000.00 and Indirect costs required amount to Rp 387,756,995.00. The total cost required for the reclamation of the 11.08 Ha land is IDR 1,714,328,995.